HIV Risk and Adolescent Behaviors in Africa - Case, Anne; Paxson, Christina (American Economic Review, 2013)
We investigate the relationship between HIV, marriage and nonmarital sexual activity, with a focus on adolescent behaviors. We use data from 45 Demographic and Health Surveys to examine how adolescent behavior among women born from 1958 to 1965 are related to the subsequent spread of HIV over time. These women were adolescents during the early 1980s, a time when HIV had started to spread but the cause was still unknown. We find that areas with currently high HIV rates had greater female education and more premarital sexual activity in the cohorts that came of age before HIV was understood.